Ink Spot Lentigo: Singular Clinical Features in a Case Series of Patients. (October 2013) - Bottoni, U.; Nisticò, S.; Amoruso, G.F.; Schipani, G.; Arcidiacono, V.; Scali, E.; Tassone, P.; Greco, M.; Amorosi, A.
Ink spot lentigo, also known as "reticulated black solar lentigo", is a melanotic macula commonly described in fair-skinned individuals on sun-exposed areas of the body. Clinically it is a darkly pigmented type of solar lentigo; herein the term "ink spot" lentigo. In contrast to common solar lentigines, ink spot lentigo is reported as a unique lesion. However usually ink spot lentigo appears among several common solar lentigines. We report a series of 5 patients who presented ink spot lentigo with typical dermoscopic pattern but singular clinical features.